Pengaruh Online Customer Review Dan Viral Marketing Terhadap Keputusan Pembelian Roti Ice Cream Roti’O (Studi Kasus Roti’O AEON Deltamas) - Yudi Sutrisna; Ajat Sudrajat (Universitas Muhammadiyah Metro, 2025)
The purpose of this study is to examine how online customer reviews and viral marketingimpact people's decisions to buy roti'o ice cream bread. This study employed a quantitativeresearch methodology. The consumers of Roti'O ice cream bread who have purchased andtried the product served as the study's population. One method of gathering data is throughsurveys with 100 responders that are directed to Roti'O ice cream customers. With SmartPLS4.0 software, partial least squares (PLS) are used in this study analysis approach to handledata. Purposive sampling was used to get this study sample. The findings of a well-structuredstudy description lead to the conclusion that viral marketing and online customer reviewspositively and significantly affect consumers' decisions to buy Roti'o AEON Deltamas icecream bread